2021
DOI: 10.1002/2211-5463.13081
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis aggravates kidney injury by upregulating STAT1 expression in a mouse model of hypertension

Abstract: Periodontitis is an autoimmune disease of periodontal tissues initiated by plaque. It is known that there is a close connection between periodontitis and CKD with hypertension, but the underlying mechanisms are unknown. STAT1 has been reported to play a regulatory role in hypertension and chronic kidney disease (CKD). Here, we investigated whether STAT1 regulates periodontitis‐mediated aggravation of kidney injury with accompanying hypertension. A hypertensive renal injury mouse model was established with Nos3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 29 publications
(52 reference statements)
1
23
0
Order By: Relevance
“…40 To date, only an animal study with transcription factor signal transducer and activator of transcription (STAT) has been carried out considering both PD and CKD. 41 The study demonstrated that STAT1 expression was augmented by periodontitis, and resulted in the upregulation of inflammatory and fibrosis genes, which aggravated hypertensive renal injuries in the mouse model, thus suggesting a new target for periodontal treatment in CKD patients. 41 Notably, 30-50% of both ESRD patients on RRT and non-dialyzed CKD patients show evidence of an active systemic inflammatory response in the form of elevated serum levels of CRP and other pro-inflammatory cytokines, like IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…40 To date, only an animal study with transcription factor signal transducer and activator of transcription (STAT) has been carried out considering both PD and CKD. 41 The study demonstrated that STAT1 expression was augmented by periodontitis, and resulted in the upregulation of inflammatory and fibrosis genes, which aggravated hypertensive renal injuries in the mouse model, thus suggesting a new target for periodontal treatment in CKD patients. 41 Notably, 30-50% of both ESRD patients on RRT and non-dialyzed CKD patients show evidence of an active systemic inflammatory response in the form of elevated serum levels of CRP and other pro-inflammatory cytokines, like IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 95%
“…41 The study demonstrated that STAT1 expression was augmented by periodontitis, and resulted in the upregulation of inflammatory and fibrosis genes, which aggravated hypertensive renal injuries in the mouse model, thus suggesting a new target for periodontal treatment in CKD patients. 41 Notably, 30-50% of both ESRD patients on RRT and non-dialyzed CKD patients show evidence of an active systemic inflammatory response in the form of elevated serum levels of CRP and other pro-inflammatory cytokines, like IL-1 and IL-6. 42 Therefore, there are 2 potential mechanisms through which the immune system and the inflammatory process may affect distant organs, including the kidneys.…”
Section: Discussionmentioning
confidence: 95%
“…Hsa-mir-21-5p [576] and PAX2 [577] are believed to be associated with FSGS. Liu et al [578], Park et al [579], Yang et al [580], Yu et al [581] and Forero-Delgadillo et al [582] mentioned that hsa-mir-21-5p, STAT3, STAT1, GATA2 and PAX2 were related to other kidney diseases. Studies have indicated that hsa-mir-21-5p [583], STAT3 [584], STAT1 [585] and GATA2 [586] plays a substantial role in hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Activated Jaks phosphorylate specific tyrosine residues of STATs, leading to STAT dimerization and translocation into the nucleus [ 33 , 34 ]. STATs then bind specific DNA sequences along with transcriptional cofactors to regulate the expression of genes involved in cell growth, differentiation, and survival, as well as apoptosis [ 29 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Nonspecific Jak signaling inhibition has been previously reported to suppress the expression of inflammatory cytokines and mitigate acute oxidative stress in renal tissue [ 40 ].…”
Section: Introductionmentioning
confidence: 99%